A quantitative analysis of double-sided surface waviness on TEHL line contacts. (May 2023) - Havaej, Peyman; Degroote, Joris; Fauconnier, Dieter
Abstract: In this paper, the effects of double-sided surface waviness on Thermo-Elastohydrodynamic Lubrication (TEHL) in line contacts are investigated deterministically through numerical simulations. The effects of surface amplitude, wavelength, relative position, and slide-to-roll ratio have been studied. The classic approach, which consists of an equivalent deformable body with superimposed surface waviness, is critically evaluated and compared to results from full two-body simulations. Under the investigated conditions, the equivalent and two-body approaches show about 17%, 21%, and 26% deviations in maximum pressure, temperature, and friction, respectively. It is demonstrated that the fundamental cause of the observed deviations, which results in a phase shift that cannot be described by the equivalent geometry, is the tangential elastic deformation of surface asperities. Graphical Abstract: ga1 Highlights: An overestimated pressure, temperature, and von Mises stress in the equivalent body with a superimposed surface profile. A significant lateral elastic deformation of the wave crests causes deviation between two-body and equivalent body results. The maximum values of pressure and temperature rise increase monotonously with increasing amplitude. The maximum von Mises stresses shift towards the surface due to the presence of waviness. The minimum and central film thickness oscillate roughly 25% when two opposing wave crests roll-slide past each other.